2016
DOI: 10.1111/and.12621
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of ginseng and ciprofloxacin ameliorates epididymo-orchitis induced alterations in sperm quality and spermatogenic cells apoptosis following infection in rats

Abstract: Korean red ginseng (KRG) may be a beneficial adjuvant along with ciprofloxacin to ameliorate devastating effects of epididymo-orchitis (EO) on male fertility. This study intends to assay the effects of KRG and ciprofloxacin on sperm quality and spermatogenic cells apoptosis in EO rats. We divided 54 adult rats into nine groups (n = 6 rats per group): control (CO), sham-operated (SH), EO (E); ciprofloxacin (C), EO-ciprofloxacin (EC), KRG (G), EO-KRG (EG), ciprofloxacin-KRG (CG) and EO-ciprofloxacin-KRG (ECG). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
3
14
0
Order By: Relevance
“…They found that ginseng induced non-significant elevation in total protein, albumin and globulin. Also, Eskandari et al (2017) found that ginseng induced non-significant elevation in total protein and globulin in rats. On the other hand, Doxorubicin plus ginseng group showed non-significant changes in total protein and albumin levels in comparison either with control group and doxorubicin group.…”
Section: Discussionmentioning
confidence: 97%
“…They found that ginseng induced non-significant elevation in total protein, albumin and globulin. Also, Eskandari et al (2017) found that ginseng induced non-significant elevation in total protein and globulin in rats. On the other hand, Doxorubicin plus ginseng group showed non-significant changes in total protein and albumin levels in comparison either with control group and doxorubicin group.…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies showed that ginseng could promote sperm quality under different experimental conditions (Park et al, ). The protective effects of ginseng on sperm quality might refer to its antioxidant impact, ROS scavenging and increase in the antioxidative defence system (Eskandari et al, ). In addition, ginseng can induce sperm hyperactivation by increasing sperm cation channel (CatSper) gene expression (Park, Kim, Kim, Park, & Chang, ).…”
Section: Discussionmentioning
confidence: 99%
“…The stock solution consisted of 100 mg dried extract per ml of sterile phosphate‐buffered saline (PBS). The extract solution was sterilised by filtration through a 0.2 µ Millipore filter (Eskandari et al, , ) .…”
Section: Methodsmentioning
confidence: 99%
“…Several preclinical studies have reported that ginseng promotes spermatogenesis, as well as improving testicular problems, sperm quality, and sperm mobility, due to be a cyclic adenosine monophosphate-responsive element modulator [15][16][17][18][19][20]. Recent reviews summarize that ginsenosides-the predominant active compounds of ginseng-may affect estrogen and androgen activity, and act as an aphrodisiac [21,22].…”
Section: Introductionmentioning
confidence: 99%